Study of the Economic Factors Affecting the Outcomes of Agricultural Education in the Municipality of Sebha in South Libya - Aridah, Ahmad (Journal of Pure & Applied Sciences, 2025)
This study aimed to identify the economic factors that affect agricultural education outcomes to meet the requirements of the labor market in the municipality of Sebha in south Libya during the period 2023. The study relied on field data of the study sample. A descriptive and quantitative analysis, means, standard deviation, and T-test were used to meet the objectives of the study. The results of the study showed that agricultural training courses, agricultural faculties, and institutes in southern Libya have a significant impact on improving the outcomes of agricultural education. The study also indicated that the level of income and agricultural investments have a significant impact on the effectiveness and efficiency of an agricultural education graduate. The study recommended holding agricultural training courses and providing agricultural loans to new farmers, improving the infrastructure of agricultural faculties and institutes, expanding the culture of agricultural education, and determining the requirements of the agricultural labor market.